The imbalance of serotonergic circuitry impairing the crop supercontractile muscle activity and the mitochondrial morphology of PD PINK1B9Drosophila melanogaster are rescued by Mucuna pruriens. (November 2018) - Solari, Paolo; Maccioni, Riccardo; Marotta, Roberto; Catelani, Tiziano; Debellis, Doriana; Baroli, Biancamaria; Peddio, Stefania; Muroni, Patrizia; Kasture, Sanjay; Solla, Paolo; Stoffolano, John G.; Liscia, Anna
Graphical abstract: Highlights: Drosophila PINK1 B9 mutant is a model for Parkinson's disease. The adult crop organ is an important and essential part of the gut. PINK1 B9 flies show morphological and functional impairment in the crop muscle. PINK1 B9 flies show an impairment in the 5-HT circuitry. Mucuna pruriens extract rescues the crop impairment. Abstract: Despite its great potentiality, little attention has been paid to modelling gastrointestinal symptoms of Parkinson's disease (PD) in Drosophila melanogaster (Dm). Our previous studies on standardized Mucuna pruriens extract (Mpe) have shown usefulness in the Drosophila model of PD. In this communication, we provide new information on the effect of Mpe on basal and serotonin treated contractions in the crop (i.e., an important and essential part of the gut) in Drosophila PD mutant for PTEN-induced putative kinase 1 (PINK1 B9 ) gene. The effect of Mpe on PINK1 B9 supplied with standard diet to larvae and/or adults, were assayed on 10–15 days old flies. Conversely from what we observed in the wild type flies, recordings demonstrated that exogenous applications of serotonin on crop muscles of untreated PINK1 B9 affect neither the frequency nor the amplitude of the crop contraction, while the same muscle parameters are enhanced following brain injections of serotonin, thus suggesting that PINK1 B9 mutants may likely have an impairment in the serotonergic pathways. Also, the mitochondrial morphology in the crop muscles is strongly compromised, as demonstrated by the transmission electron microscopy analysis. The Mpe treatment rescued the crop muscle parameters and also the mitochondrial morphology when supplied to both larvae and adults. Overall, this study strengthens the relevance of using PINK1 B9 Dm as a translational model to study the gastrointestinal symptoms in PD and also confirms the useful employment of M. pruriens for PD treatment.